Mapping the Vertical Distribution of Population and Particulate Air Pollution in a Near–Highway Urban Neighborhood: Implications for Exposure Assessment - Wu, Chih-Da (J Expo Sci Environ Epidemiol, 2013)
Due to data collection challenges, the vertical variation in population in cities and particulate air pollution are typically not accounted for in exposure assessments, which may lead to misclassification of exposures based on elevation of residency. To better assess this misclassification, the vertical distribution of the potentially highly exposed population (PHEP), defined as all residents within the 100-m buffer zone of above-ground highways or the 200-m buffer zone of a highway-tunnel exit, was estimated for four floor categories in Boston’s Chinatown (MA, USA) using the three-dimensional digital geography (3DIG) methodology. Vertical profiles of particle number concentration (7–1000 nm; PNC) and PM(2.5) mass concentration were measured by hoisting instruments up the vertical face of an 11-story (35-m) building near the study area throughout the day on multiple days. The concentrations from all the profiles (n=23) were averaged together for each floor category. As measurement elevation increased from 0 to 35 m PNC decreased by 7.7%, compared to 3.6% for PM(2.5). PHEP was multiplied by the average PNC for each floor category to assess exposures for near-highway populations. The results show that adding temporally-averaged vertical air pollution data had a small effect on residential ambient exposures for our study population; however, greater effects were observed when individual days were considered (e.g., winds were off the highways).